Indices of physical fitness in rhytmic gymnastics athletes - Jiang, Y.; Han, H. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Rhythmic gymnastics uses the body as a tool for expression and choreographed beauty. Athletes use various body movements and beautiful voices to create a competitive sport that combines technology and art. This high-level sports performance set results from much targeted fitness training. Yet, the sport lacks research relating fitness to the difficulties of the new rules. Objective: This paper explores the choreographic differences in rhythmic gymnastics under the current rules. The differences in athletes` body fitness are also evaluated. Methods: The fitness indices of 120 rhythmic gymnasts were evaluated by a developed method encompassing the upper body, trunk and lower limbs. A general analysis of the movement organization characteristics of Chinese rhythmic gymnasts was also performed. Armed with these data, the mathematical statistics method was adopted to conduct empirical research. Results: The 10-second long jump, standing jump, lifting, plank, and other 10-s performances in elite athletes were significantly more expressive than those in ordinary athletes (P<0.01). In the lifting test, elite athletes were significantly better than ordinary athletes (P<0.01). There was a significant difference between elite and ordinary athletes in the plank stand (P<0.05). There was no significant difference in the remaining individual scores. Conclusion: The critical period of the upper limb development of rhythmic gymnasts is significantly lagged compared to the lower limbs. The artistic arrangement of rhythmic gymnastics is fundamental to its good presentation. The innovations and diversified changes evidenced an advance in rhythmic gymnastics that athletes must absorb to achieve better competitive results.